COMBATTING CHILDHOOD OBESITY: INNOVATIVE STRATEGIES IN PHYSICAL EDUCATION TO PROMOTE HEALTHY LIFESTYLES (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the escalating challenge of childhood obesity and the pivotal role innovative physical education (PE) strategies play in combating this public health crisis. Through a detailed exploration of literature and successful case studies, it highlights how schools can leverage cutting-edge teaching methods, technology, and nutritional education within PE programs to promote healthy lifestyles and reduce obesity rates among children. The integration of gamification, active engagement practices, and a holistic health approach demonstrates significant potential in enhancing student participation in physical activities while fostering an understanding of nutritional well-being. The findings underscore the necessity for robust policy support and resources to implement and sustain these innovative strategies, emphasizing the crucial contribution of physical education to public health and the well-being of future generations.